Comparative Anatomical and Histological study of gall bladder in Mallard (Anas platyrhynchos) and Broiler fowl (Gallus gallus ) - Suadad Abdullh Abdulqader; Huwait, Abduljabar .R.Huwait; Nadihm .A.shehan (University of Thi-Qar Journal of agricultural research, 2023)
The current study was investigated anatomical and histological description of gall bladder of two specious which different in nutrition and life habitat Mallard (Anas platyrhnchos) aquatic life bird, and broiler fowl (Gallus gallus) wild life bird ,used ten bird of each specious ,anatomical result founded the gall bladder is located at the visceral surface right lobe of liver at right side of abdominal cavity, and composed of three parts head, neck and body, gall bladder in both specious appeared with dark green color. Gall bladder of mallard has balloon shape more elongated organ while in Gallus gallus is pear shape, the mean weight of gall bladder in mallard (1.91±0.56 g) , length (3.07±0.505 cm) and width (3.07±0.5 cm ) while broiler fowl weight of gall bladder (8.24±2.88 g), length (3.31±0.8 cm)and width (3.56±1.32 cm ) .Histologically; Gall bladder in mallard has three main layers: tunica mucosa, tunica muscularis and tunica adventitia ,tunica mucosa which lined by simple columnar epithelium non-ciliated with goblet cells and the lamina propria-submucosa composed of loos connective tissue , tunica muscularis was a thick layer of muscles (smooth muscles) and adventitia made of loos connective tissue , while gall bladder of Gallus gallus domesticus has three layer; tunica mucosa, lamina propria -submucosa, tunica muscularis and adventitia , tunica mucosa which lined by simple columnar epithelia non- ciliated without goblet cells , with present lamina propria -submucosa fused with lamina propria ,and thin layer of tunica muscularis and adventitia made of loos connective tissue .